Reading Bachtin through Cassirer: On the Roots of Bachtin’s Cultural Theory within the Philosophy of Symbolic Forms (KULT_online, 2010)
In his philosophical dissertation Das Werden des Menschen im Wort. Eine Studie zur Kulturphilosophie Michail M. Bachtins (The Becoming of the Human in the Word: A Study of Michail M. Bachtin’s Cultural Philosophy), published in 2009, Wolfram Eilenberger investigates Bachtin’s writings on the novel as an anthropology of words (cf. p. 14). By contextualising Bachtin’s work in relation to coeval philosophical schools – especially to Cassirer’s Philosophy of Symbolic Forms – Eilenberger demonstrates a coherence within the manifold bachtinian opus. At the end of the study Eilenberger makes the case that the contemporary relevance of Bachtin’s work lies in his polyphone theoretical style (cf. p. 253). However, this final thesis on the topicality of Bachtin’s work isn’t discussed in depth.